Use of acoustic myography to evaluate forelimb muscle function in retriever dogs carrying different mouth weights - Weber, Melissa A.; Manfredi, Jane M.; Tomlinson, Julia E. (Frontiers in Veterinary Science, 2022)
Objectives: To evaluate the effect of mouth weight on gait and relative function of forelimb muscles in retriever hunting dogs as a possible explanation for biceps tendinopathy. Methods: Ten sound retriever dogs underwent acoustic myography, measuring efficiency (E-score), spatial summation (S-score), and temporal summation (T-score) during walk and trot on a pressure sensitive walkway while carrying a 0 lb. (0 kg); 1 lb. (0.45 kg); and 3.2 lb. (1.45 kg) mouth weight. Gait data included total pressure index (TPI), step length and stance time. Statistics included a mixed effects model significant at p<0.05. Results: Forelimb TPI increased with increasing weight. There was no significant change in individual muscle parameters in response to weight. Significance was found on between-muscle comparison. For walk, T-score was significantly lower in triceps versus brachiocephalicus with 1 lb., not with 3.2 lb., S-score was significantly lower in the biceps at 0 lb. and 1 lb. and triceps at 0 lb. when compared to brachiocephalicus, E-score was significantly lower in deltoideus versus brachiocephalicus at trot with l lb. and 3.2 lb. There was an overall significant effect of muscle on T-score at trot, but no individual muscle comparison was significant. Conclusion: Forelimb load increases with mouth weight. Deltoideus had a longer contraction time in response to increasing weight at trot when compared to brachiocephalicus. The biceps muscle did not show increased work in response to increasing weight. Clinical relevance: The underlying etiology of biceps tendinopathies in retriever dogs remains uncertain but is not due to increasing weight.